(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ With the rapid growth of cities, the functions of the police have been affected. The increase in the use of Information and Communication Technologies (ICT), backed by access to a large amount of public and police information, represents an opportunity for improving the fight against crime and to manage time more efficiently. Methodology/approach/design ”“ This paper analyzes the role played by ICT as tools for reducing crime in the city of Lima (Peru). Findings ”“ The results obtained show that a better level of ICT infrastructure and greater access to information sources through the Internet in police stations discourages the level of crime. Practical implications ”“ In addition, these better levels of ICT presence in police stations generate a higher level of interaction and exchange of data and information between neighboring police stations.